High surgeon volume and positive surgical margins can predict the risk of biochemical recurrence after robot-assisted radical prostatectomy. (September 2019) - Porcaro, Antonio Benito; Tafuri, Alessandro; Sebben, Marco; Amigoni, Nelia; Processali, Tania; Pirozzi, Marco; Rizzetto, Riccardo; Shakir, Aliasger; Corsi, Paolo; Tiso, Leone; Cerrato, Clara; Migliorini, Filippo; et al.
Background: The aim of this study was to determine whether any clinical factors are independent predictors of positive surgical margins (PSM), and to assess the association of PSM and biochemical recurrence (BR) after robot-assisted radical prostatectomy (RARP). Methods: The population included cases with negative surgical margins (control group) and patients with PSM (study group). Tumor grade was evaluated according to the International Society of Urologic Pathology (ISUP) system. A logistic regression model assessed the independent association of factors with the risk of PSM. The risk of BR was assessed by Cox's multivariate proportional hazards. Results: A total of 732 consecutive patients were evaluated. Extend pelvic lymph node dissection (ePLND) was performed in 342 cases (46.7%). Overall, 192 cases (26.3%) had PSM. The risk of PSM was positively associated with the percentage of biopsy positive cores (BPC; odds ratio, OR = 1.012; p  = 0.004), extracapsular extension (pT3a; OR=2.702; p  < 0.0001), invasion of seminal vesicle (pT3b; OR = 2.889; p  < 0.0001), but inversely with body mass index (OR = 0.936; p  = 0.021), and high surgeon volume (OR = 0.607; p  = 0.006). Independent clinical factors associated with the risk of BR were baseline prostate-specific antigen (PSA; hazard ratio, HR = 1.064; p  = 0.004), BPC (HR = 1.015; p  = 0.027), ISUP biopsy grade group (BGG) 2/3 (HR = 2.966; p  = 0.003), and BGG 4/5 (HR = 3.122; p  = 0.022). Pathologic factors associated with the risk of BR were ISUP group 4/5 (HR = 3.257; p  = 0.001), pT3b (HR = 2.900; p  = 0.003), and PSM (HR = 2.096; p  = 0.045). Conclusions: In our cohort, features related to host, tumor, and surgeon volume are associated with the risk of PSM, which is also an independent parameter predicting BR after RARP. The surgical volume of the operating surgeon is an independent factor that decreases the risk of PSM, and, as such, the risk of BR.